Removal of Iron and Total Chromium Contaminations in Landfill Leachate by Using Electrocoagulation Process - Mahmad, Mohd Khairul Nizam; Rozainy, Mohd Remy; Abustan, Ismail; Baharun, Norlia
This research work involves the study removal of Iron and Total Chromium by electrocoagulation process. This project focused on leachate landfill from Pulau Burung, Nibong Tebal, Penang as an electrolyte solution.